Conducting Polymers as Anode Buffer Materials in Organic and Perovskite Optoelectronics. Issue 3 (9th November 2016) - Ahn, Soyeong; Jeong, Su‐Hun; Han, Tae‐Hee; Lee, Tae‐Woo
Abstract : This review focuses on the importance and the key functions of anode interfacial layers based on conducting polymers in organic and organic–inorganic hybrid perovskite optoelectronics. Insertion of a buffer layer between electrode and semiconducting layers is the most common and effective way to control interfacial properties and eventually improve device characteristics, such as luminous efficiency in light‐emitting diodes and power conversion efficiency in solar cells. Conducting polymers are considered as one of the most promising materials for future organic and organic–inorganic hybrid electronics because of advantages such as a simple film‐forming process and ease of tailoring electrical and physical properties; as a result, using these polymers is compatible with the production of large‐area, low‐cost, and solution‐processed flexible optoelectronic devices. This review introduces the limitations of anode buffer layers based on conducting polymers and then we will provide recent research trends of material engineering to overcome these problems. Abstract : Conducting polymers are widely used as an anode buffer layer for organic and organic–inorganic hybrid perovskite (OIHP) optoelectronics. Engineering of various materials is reviewed and discussed to overcome limitations of conventional conducting polymers, and their applications as a conducting polymer‐based anode buffer layer in organic and OIHP light‐emitting diodes and solar cells.